Effects of a functional training program in physical qualities of futsal athletes - Moura, Dagnou Pessoa de [UNESP]; Oliveira da Silva, Tiago Aparecido; Garcia, Vinicius Brancaglion; Santos, Julio Wilson dos [UNESP] (Inst Brasileiro Pesquisa & Ensino Fisiologia Exercicio-ibpefex, 2018)
Physical training is based on a consistent and safe prescribing exercises that allow the simulation of the human body in a way able to develop all the qualities of the musculoskeletal system, such as speed, strength, body balance coordination, flexibility, laterality, cardio endurance and neuromuscular besides maintaining the center of gravity of the body. Futsal is a sport that has growth most in recent years, the sport has characteristic physical effort of high intensity and short duration, which does need a good physical preparation. Among the important physical abilities in futsal are agility, speed, flexibility, power of lower limbs and abdominal strength. An experimental research with a quantitative approach was carried out in order to verify the influence of functional training in physical abilities used for futsal players. For this the following protocols were used: 20-meter shot for speed; standing long jump test for potency of the lower limbs; Wells bank for flexibility; Semo test for flexibility; abdominal muscle endurance test. Statistical analysis Student T test for dependent data, which was adopted a significance level of p <= 0,05 was adopted. This study was conducted with 10 volunteers (age 15.33 +/- 0.5 years, it lasted 3 months functional training being performed twice a week. The results were statistical improvement in physical abilities of abdominal strength, flexibility, agility, speed and power of the lower limbs. We conclude that a functional training program influences the improvement of the physical capabilities of futsal.
Keywords: Functional training; Futsal; Physical capabilities